Eksistensi dan Implementasi Asas Pacta Sunt Servanda dalam Sistem Hukum Perjanjian - Dali, Meilina Widya; Mahmud, Yuliyana Imelda; Hasan, Eka Rachmatia; Talamati, Alisya Aprillia; Tuu, Rozzanna Adelia D.; Monoarfa, May Lhing Aqmalia; Nakuu, Sisi Lianti; Richard, Kafka; Ali, Mohammad Fitra R.; Rias, Radit U.; Kango, Ishak; Randy Ibrahim (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
his research is motivated by the significance of the principle of pacta sunt servanda as a fundamental doctrine in contract law that ensures binding force and legal certainty in contractual relationships, while also facing challenges in its application within modern legal practice. The purpose of this study is to examine the existence of the pacta sunt servanda principle within the Indonesian contract law system, to analyze its legal foundations and scholarly perspectives, and to explore its implementation in judicial practice. This study employs a qualitative research method with a normative juridical approach, conducted through library research on statutory regulations, legal doctrines, and relevant court decisions. The findings indicate that the principle of pacta sunt servanda holds a strong normative position, particularly as stipulated in Article 1338 of the Indonesian Civil Code, and is consistently used as a basis for judicial consideration in resolving contractual disputes. Nevertheless, the application of this principle is not absolute, as it must be integrated with the principles of good faith, propriety, and justice to safeguard the balance of interests between the parties. This research concludes that the principle of pacta sunt servanda remains relevant and effective as a cornerstone of contract law, provided it is applied proportionally and contextually. Therefore, the enforcement of contract law should consistently balance legal certainty with substantive justice in contractual practice.